Autophagy in Stem Cell Biology: A Perspective on Stem Cell Self-Renewal and Differentiation - Xihang Chen; Yunfan He; Feng Lu (Hindawi Limited, 2018)
Autophagy is a highly conserved cellular process that degrades modified, surplus, or harmful cytoplasmic components by sequestering them in autophagosomes which then fuses with the lysosome for degradation. As a major intracellular degradation and recycling pathway, autophagy is crucial for maintaining cellular homeostasis, as well as for remodeling during normal development. Impairment of this process has been implicated in various diseases, in the pathogenic response to bacterial and viral infections, and in aging. Pluripotent stem cells, with their ability to self-replicate and to give rise to any specialized cell type, are very valuable resources for cell-based medical therapies and open a number of promising avenues for studying human development and disease. It has been suggested that autophagy is vital for the maintenance of cellular homeostasis in stem cells, and subsequently more in-depth knowledge about the regulation of autophagy in stem cell biology has been acquired recently. In this review, we describe the most significant advances in the understanding of autophagy regulation in hematopoietic and mesenchymal stem cells, as well as in induced pluripotent stem cells. In particular, we highlight the roles of various autophagy activities in the regulation of self-renewal and differentiation of these stem cells.